Pelatihan Penyusunan Perencanaan Bisnis dan Periklanan pada Kelompok Pemeliharaan Ulat Jerman Srikandi Berdikari - Taufan, Gullit Tornado; Wicaksono , Julien Arief; Suharsono, Degita Danur; Kamal , Mushthofa; Murti, Ghanesya Hari (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2021)
Srikandi Berdikari is a group of youth who focuses on breeding superwoms (zhopabas morio) located in Grujugan, Bondowoso. This is a relatively new business activity in which any means of assistances are needed by the group in order to develop the business. Through this community service activity, it is expected that the group can benefit from the activity which focuses on (1) developing a business plan by using Business Model Canvas (BMC), (2) producing business profile, and (3) designing product label and packaging. The activities were done both online through virtual meeting due to the current situation of Covid-19 pandemic and offline by visiting the business site by considering the Covid-19 protocol. The results of the community service activity show the that the group is able to develop a business plan as well as producing a business profile and product label.